Exhibiting electricity - Beauchamp, K. G. (Institution of Electrical Engineers, 1997)
This unusual book traces the history of public and technical exhibitions, from their origins in the late 18th Century to present day, and, particularly, how they have reflected the progress of science and technology especially electrical technology). Not only does the author show how electrical innovation and manufacture have been presented to the wider public through this period, but he also shows how the exhibitions themselves have required technological advice.